O design de superfície aplicado na valorização do território de Porto Alegre - Medeiros, Mariana de Lemos (Universidade do Vale do Rio dos Sinos, 2012)
According to a methodology used to design projects, where research in graphic design, surface design and territorial design are developed, this work aims to join two areas: the territorial and the surface design. Case studies evaluating existent projects and a chapter about the city of Porto Alegre, object of this work, are also based here. From the territorial design, the objective is to identify the most representative elements and icons of the city of Porto Alegre to achieve the final outcome – the development of patterns and its application in goods, for export and local usage. The surface design project developed through the view of the territorial design work as a strategy to improve the value of the city image, strengthening the city identity locally and globally.
Keywords: Design territorial; Design de superfície; Estampas; Porto Alegre; Territorial design; Surface design; Patterns